Innovation of Jalan Rusak Lapor Dewe Application at the East Java Bina Marga Public Works Office - Putri, Thersa Armenia; Harmawan, Bagus Nuari (Journal La Sociale, 2024)
The East Java Bina Marga Public Works Office created an innovation called JALAK LOEWE (Jalan Rusak Lapor Dewe). The innovation is used to facilitate the community in complaining about road damage. This research aims to discuss the public service innovation launched by the East Java Bina Marga Public Works Office through the JALAK LOEWE application. The research method used in this research is qualitative research with a case study approach. In obtaining data, researchers collect through observation, interviews, and documentation. The results of this study refer to seven innovations in digital public services in (Bertot, Estevez, & Janowski, 2016), namely: Transparent, Participatory, Anticipatory, Co-Created, Personalized, Context-aware, Context-smart. Based on the findings obtained, it explains that there are several indicators that have been running quite well, but there are still other indicators that have not been fulfilled.